Cell density regulates cancer metastasis via the Hippo pathway. (December 2015) - Sharif, Ghada M; Wellstein, Anton
Metastatic spread of cancer cells from the primary tumor site to distant organs is the major cause of death in cancer patients. To disseminate, cancer cells detach from the primary tumor, enter the blood stream and extravasate at distant organ sites such as the liver, lung, bone or brain. While cancer cells are known to evade contact inhibition during growth in culture, we found that cell density is still sensed and can signal through the Hippo pathway effectors LATS1 and YAP. These effectors control cancer cell invasive behavior into stromal tissues, expression of cytokines that recruit inflammatory cells and progression toward metastatic spread. In this perspective, we discuss the drivers and the significance of pathways controlled by cell growth density.